Are consumers planning consumption according to an Euler equation? - Lena Dräger (Hamburg University, Department Socioeconomics, 2016)
Evaluating a new survey dataset of German consumers, we test whether individual consumption plans are formed according to an Euler equation derived from consumption life-cycle models. Estimating several consumption Euler equations, the results are mostly in line with the theory: We find evidence of consumption smoothing, since individual current and planned spending are positively correlated. In addition, current spending is positively correlated with both quantitative and qualitative inflation expectations, and negatively with quantitative nominal interest rate expectations. Overall, this results in a negative link between current spending and implied real interest rate expectations, where the weaker effect of nominal interest rate expectations might be due to the current zero-lower-bound environment. As expected, the effect of perceived real interest rates is most pronounced for consumers' who are active on financial markets. Finally, economic news on inflation and financial market developments observed by the consumer strengthen the effects of their interest rate and inflation expectations on current spending.
Keywords: D12; D14; D84; C83; 330; Euler equation; consumers; macroeconomic expectations; consumption plans; survey micro data